1976
DOI: 10.1111/j.1464-410x.1976.tb06703.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Papilloma of the Lower Urinary Tract

Abstract: A study of 35 cases of inverted papilloma of urothelium confirms that it is a distinctive entity and typically benign. These lesions occur mainly in males, may be multiple, and are sometimes situated elsewhere than in or near the trigone, which is their characteristic site. Their precise histogenesis remains uncertain. It must be stressed that not all transitional cell tumours of inverted pattern are of this type; some will have the appearance of and behave as malignant tumours. The same diagnostic criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…Recently, however, several authors have expressed doubt as to the entirely benign nature of this tumor. Cameron and Lupton [8] noted that an inverted pattern was not confined to benign lesions, but was seen also in certain carcinomas, all or part of which showed this structure. Lazarevic and Garret [26] and Whitesel [41] showed papillary malignant transforma tion of the surface epithelium of inverted papillomas (type II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, several authors have expressed doubt as to the entirely benign nature of this tumor. Cameron and Lupton [8] noted that an inverted pattern was not confined to benign lesions, but was seen also in certain carcinomas, all or part of which showed this structure. Lazarevic and Garret [26] and Whitesel [41] showed papillary malignant transforma tion of the surface epithelium of inverted papillomas (type II).…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 200 cases of inverted papilloma and 13 cases of inverted papillary tumor associated with malignancy have been reported to date, only 4 [6,7,10,24] and 1 [8] case, respectively, have been of recurrence. Furthermore, no invasiveness or metastasis has been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 51 cases originally diagnosed as inverted papilloma of the uri nary tract, only 37 proved to be true inverted papillomas (see figure). Misdiagnoses, seen at all 7 pathology departments, were pTaGl-2A transitional cell carcinoma (9), p T l G 2 A trans itional cell carcinoma (2), Brunn's cell nests (2) and polyploid cystitis (1).…”
Section: Diagnosismentioning
confidence: 99%
“…Reported cases of transitional cell carcinoma of the bladder with inverted proliferation are shown in Table 1 .133, 4,6,9,1 The literature characterizes these tumors as occurring in males, usually as small lesions near a ureteral orifice, and tending to be highly agg r e s s i~e .~,~,~~ Furthermore, it is reported that a tendency toward increasing cellular anaplasia with increasing depth of invasion may give a deceptively benign histological appearance in biopsy specimens. However, in spite of having bulky tumors with unfavorable histology, our 2 female patients have been successfully treated with bladder-sparing surgery, perhaps because both tumors were pedunculated with a relatively narrow stalk.…”
Section: Disc Ussl Onmentioning
confidence: 99%